2018
DOI: 10.1111/jhn.12593
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FTO rs9930506 on obesity and interaction of the gene variants with dietary protein and vitamin E on C‐reactive protein levels in multi‐ethnic Malaysian adults

Abstract: The presence of the risk allele (G) of FTO rs9930506 was not associated with an increased risk of obesity. Malaysian Indians had a significantly higher frequency of the risk allele (G). Indian participants expressed higher atherogenic phenotypes compared to Chinese and Malays. FTO rs9930506 may interact with dietary protein and vitamin E and modulate hsCRP levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Detailed information on the study design and methods can be found in our earlier publication [16]. Therefore, with respect to assessment of anthropometric parameters, dietary nutrients analysis, and physical activity level assessment, we refer the readers to our earlier publication [16].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed information on the study design and methods can be found in our earlier publication [16]. Therefore, with respect to assessment of anthropometric parameters, dietary nutrients analysis, and physical activity level assessment, we refer the readers to our earlier publication [16].…”
Section: Methodsmentioning
confidence: 99%
“…Low-density lipoprotein (LDL) cholesterol was calculated using the Friedewald formula: LDL cholesterol = total cholesterol − ((triglyceride/5) + HDL cholesterol) [18]. This information has been reported in our earlier publication [16]. This study investigates ADRB2 rs1042713 gene polymorphism in the same population with the aim to evaluate (i) the effect of ADRB2 rs1042713 on obesity and obesity-related anthropometric and blood biochemical parameters and (ii) the influence of diet on the association between ADRB2 rs1042713 and obesity phenotypes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use a logical sequence when listing the methods that you used. Try to do this following a chronological sequence, as shown in recently published examples .…”
Section: Writing the Methodsmentioning
confidence: 99%
“…This study is nested in a broader study investigating the association of SNP in fat mass and obesity-associated ( FTO ) gene with obesity traits and their interaction with dietary factors in Malaysian adults of three different ethnic groups. We found significant interaction between FTO rs9930506 with dietary protein and vitamin E on high-sensitivity C-reactive protein (hsCRP) levels ( 28 ) . Strong association of FTO gene and obesity-related traits have been consistently observed in studies involving various populations worldwide ( 29 – 31 ) .…”
mentioning
confidence: 99%